Mental Health Conditions Among E-Learning Students During the COVID-19 Pandemic - Rutkowska, Anna; Cieślik, Błazej; Tomaszczyk, Agata; Szczepańska-Gieracha, Joanna (Frontiers in Public Health, 2022)
Aim: The COVID-19 pandemic has forced the education system to undergo changes, which have also affected universities. E-learning became the main form of education, reducing interpersonal contacts, which could affect the mental well-being of students. The aim of this study was to investigate the prevalence of depressive symptoms and the level of perceived stress during e-learning among Polish students and to identify the factors for predicting higher levels of depression symptoms. Methods: The study included 753 participants with a mean age of 22.47 (±4.02) years. The Perception of Stress Questionnaire (PSQ) and Beck Depression Inventory (BDI-II) were used to measure the severity of stress and level of depression. Furthermore, our own survey was used to assess the impact of e-learning on various aspects of life. To examine how much stress can explain a statistically significant amount of variance in depression, three-step hierarchical multiple regression was used. In addition, our own questionnaire was used to assess the impact of e-learning on education, social contacts and technical abilities. Results: A total of 58% of the students characterised by an increased level of stress. 56% show symptoms of depression and 18% of the participants had suicidal thoughts. The most significant predictor of depression is high stress levels and factors related to e-learning: isolation from friends and acquaintances, negative impact on level of knowledge, reduced motivation to learn, and worsening grades.This predictors may explain about 66% of the variance of depression. Conclusion: Universities should implement interventions and educational programmes, providing ad hoc assistance in the form of individual or group meetings with a psychologist (also in a remote form) and organising workshops and webinars on strategies for managing stress.